2005
DOI: 10.1007/s10634-005-0053-0
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties and Coordination Interaction of d 0 Metallocenes with Unsaturated Hydrocarbons

Abstract: One of the most promising approaches to an understanding of the nature and properties of frontier orbitals of organometallic π complexes of Group IVB metalsmajor components of catalysts of a large number of organic syntheses-involves generation and study of electronically excited and ground redox states of molecules [1-6]. However, fundamental processes, such as energy and electron transfer, and properties of electronically excited states of organometallic compounds have been little studied partly due to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In fact, the bent metallocenes of the IVb family (Ti, Zr and Hf) are known to exhibit rich photophysical properties . Several theoretical works addressed the electronic structure of such species, and it was quickly established that the nature of the luminescent excited state was a nonlocalized triplet ligand-to-metal charge-transfer (LMCT). , Subsequently, numerous electrochemical, , photochemical, and photophysical , studies were reported, including rare examples of luminescence arising from species in solutions. , The Ph 2 P-containing mononuclear complex 1 in 2MeTHF at 77 K exhibits a strong luminescence centered at 659 nm (Figure ). However, this luminescence is absent at 298 K, which is common to most complexes investigated so far in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the bent metallocenes of the IVb family (Ti, Zr and Hf) are known to exhibit rich photophysical properties . Several theoretical works addressed the electronic structure of such species, and it was quickly established that the nature of the luminescent excited state was a nonlocalized triplet ligand-to-metal charge-transfer (LMCT). , Subsequently, numerous electrochemical, , photochemical, and photophysical , studies were reported, including rare examples of luminescence arising from species in solutions. , The Ph 2 P-containing mononuclear complex 1 in 2MeTHF at 77 K exhibits a strong luminescence centered at 659 nm (Figure ). However, this luminescence is absent at 298 K, which is common to most complexes investigated so far in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The observed luminescence is a forbidden triplet-sin glet transition, i.e., phosphorescence in nature, as fol lows from our experiments on triplet-triplet energy transfer to unsaturated hydrocarbons (olefines, diens, etc.) [10,[13][14][15]. This tendency towards changing the spectral and luminescent properties is preserved in the related structurally modified Ti, Zr, and Hf complexes (upon a change in the ligand sphere architecture).…”
Section: Spectral and Luminescent Properties Of Cp 2 MCL 2 Metallocenesmentioning
confidence: 99%
“…The need of determining the ener gies, Е T , of α and β olefins originated from studies of photosensitized cis-trans isomerization of the latter 20, 21 and from the use of olefins as non phosphorescing accep tors of triplet excitation. [22][23][24][25] The energies of the lowest lying triplet levels of some α and β olefins were mea sured using nonradiative T-T energy transfer. 22 Olefins and dienes are characterized by high energy singlet states and large S 1 -T 1 splitting; 26,27 they are not involved in the redox and electron transfer reactions under the experi mental conditions, thus being convenient triplet accep tors.…”
mentioning
confidence: 99%